(untitled) - Du Plessis, J. J. P.

A single stage dry/wet dephlegmator: development, performance evaluation and application in a hybrid ACC at CSP or NGCC Scale. (Stellenbosch : Stellenbosch University, 2021)
Thesis (PhD)--Stellenbosch University, 2021.